(untitled) (El-Wahat Journal for Research and Studies, 2026)
This study examines women’s voluntary work in the Mozabite community, exploring whether it is an individual initiative or a cultural and religious tradition. Field research was conducted through interviews with women volunteers from the “Tamsiridin” organization, chosen as a model for this study. The findings reveal that this organisation forms the core of women’s voluntary work in the community. It transformed women’s voluntary work from isolated individual acts into an institutional and social practice that was once exclusively for men. Thanks to the "Tamsiridin" organization, women have gained the opportunity to assert their presence as active and productive members of society. Women now contribute to the construction, stability, and continuity of the social system alongside men.